A pictorial identification key for Mediterranean and Middle Eastern Phlebotomus sand flies - Akhoundi, Mohammad; Maroli, Michele; Gradoni, Luigi; Izri, Arezki; Dedet, Jean-Pierre; Votýpka, Jan; Guernaoui, Souad; Benikhlef, Razika; Eddaikra, Naouel; Bates, Paul; Sereno, Denis; Depaquit, Jérôme (Scientific reports, 2025)
Given the significance of leishmaniasis as a neglected parasitic disease-ranking second in mortality and fourth in morbidity among vector-borne diseases-and the prominence of the Mediterranean and Middle East regions as key areas for leishmaniasis incidence, the study and precise morphological identification of sand flies, the proven vectors of the disease, is crucial. Unfortunately, despite this importance, there are few reliable references or identification keys for the morphological identification of sand flies in the Middle East and Mediterranean regions. Some are outdated and no longer valid or remain local (restricted to a country). To date, no comprehensive study has been conducted on the sand fly fauna and their morphological characterization across these regions. In response to this gap, we present a comprehensive pictorial identification key for male and female Phlebotomus species of Middle East and Mediterranean areas. The key includes 720 selected photos and illustrations demonstrating discriminative morphological features out of 2,000 collected. Furthermore, a collection including descriptive morphological criteria of sand flies, first description of Phlebotomus species, a comprehensive checklist of Phlebotomus species accompanied by their distribution map across Middle Eastern and Mediterranean countries, as well as extensive information on their morphometry, ecology, medical relevance, synonymy, atypical forms and morphology of female Adlerius species are given. Finally, we provide an online pictorial dichotomous key to facilitate field application.
Keywords: Online dichotomous key; Male; Středomoří; Phlebotomus; Leishmaniasis; mužské pohlaví; Morphological identification; hmyz - vektory; Sand fly vectors; Pictorial identification key; Střední východ; Animals; ženské pohlaví; zvířata; Insect Vectors; leishmanióza; Mediterranean Region; Female; Middle East